Association of multiple dietary metal intake with cardiovascular-kidney-metabolic syndrome: a cross-sectional study based on NHANES 2003–2018 - Hu, Sihan; Wei, Baojian; Zhang, Aihua (Frontiers in Nutrition, 2025)
BackgroundCardiovascular-kidney-metabolic (CKM) syndrome is a complex condition that encompasses cardiovascular, renal, and metabolic disorders. Dietary metal intake plays a crucial role in maintaining normal physiological functions. This study aims to examine the relationship between dietary intake of multiple metals and CKM syndrome.MethodsWe analyzed data from 15,233 participants aged 20–79 years in the National Health and Nutrition Examination Survey (NHANES) 2003–2018. Dietary metal intake included nine metals: potassium (K), calcium (Ca), magnesium (Mg), phosphorus (P), iron (Fe), copper (Cu), zinc (Zn), and selenium (Se). CKM syndrome was classified into non-advanced (stages 0–2) and advanced (stages 3–4) stages. We employed weighted logistic regression, restricted cubic splines (RCS) regression, weighted quantile sum (WQS) regression, and quantile-based g computation (qgcomp) models to evaluate the associations between individual metal intake and metal intake mixtures with CKM stages. Subgroup analysis was used to explore potential interaction effect between metal intake and other variables.ResultsWeighted logistic regression models showed that Q2 (≤0.80–1.12 mg/d) (OR = 0.74, 95% CI = 0.60, 0.92), Q3 (≤1.12–1.53 mg/d) (OR = 0.74, 95% CI = 0.58, 0.93) and Q4 (>1.53 mg/d) (OR = 0.73, 95% CI = 0.55, 0.95) groups of Cu intake were significantly associated with a reduced incidence of advanced CKM stages compared with Q1 (≤0.80 mg/d) group. The RCS regression models indicated that higher Cu intake was significantly associated with a lower risk of advanced CKM stages (p for overall < 0.05). WQS regression and qgcomp models did not reveal significant effect of the mixture. Subgroup analysis found that the effect of Cu was robust in various subgroups.ConclusionIn conclusion, higher dietary intake Cu was linked to a reduced prevalence of advanced CKM stages in the U. S. adult population.